Stand up for Alabama : Governor George Wallace - Frederick, Jeff, 1963- (Modern South., 2007)
Whereas other studies have focused on George Wallace?s career as a national figure, Stand Up for Alabama provides a detailed, comprehensive, and analytical study of Wallace?s political life that emphasizes his activities and their impact within the state of Alabama. Jeff Frederick answers two fundamental questions: What was George Wallace?s impact on the state of Alabama? Why did Alabamians continue to embrace him over a twenty-five year period? Using a variety of sources to document the state?s performance in areas including mental health, education, conservation, prisons, and industrial deve.